Childhood and disability in the Nordic countries : being, becoming, belonging - Rannveig Traustadóttir, 1950- (Studies in childhood and youth., 2015)
This unique collection brings together seventeen leading Nordic scholars to offer a series of in-depth, research-based studies on disabled children and young people in Scandinavia. The first comprehensive scholarly text to focus on the many aspects of growing up with a disability, this volume presents the latest research from Denmark, Finland, Iceland, Norway and Sweden, all of which have an international reputation for progressive welfare and disability policies with regard to children and families. It is based on the belief that in order to understand the lives of disabled children and young people it is important to combine social perspectives on disability studies with the social science of childhood and the human rights approach of the UN Conventions on the Rights of Persons with Disabilities and on the Rights of the Child. Many of the contributions focus on the experiences of the children themselves, with an emphasis on understanding the impact on their lives of social and environmental factors, cultural processes, and policy frameworks and definitions. Exploring a range of issues including theories and history of childhood disability, cultural images and identity formation, interaction and inclusion, and families and services, this collection will be essential reading for those interested in childhood and disability.